2022
DOI: 10.3389/fpubh.2022.820270
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequalities in Young People's Mental Distress During the COVID-19 Pandemic: Do Psychosocial Resource Factors Matter?

Abstract: The COVID-19 pandemic disproportionately affected young people aged 16–25 years and has brought about a major increase in mental health problems. Although there is persisting evidence regarding SES differences in mental health status, there is still little knowledge of the processes linking SES to young people's mental health, in particular during the current pandemic. Guided by a stress process model this study examines the role of different psychosocial resource factors in mitigating the vulnerability to men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 75 publications
(126 reference statements)
3
25
0
1
Order By: Relevance
“…Research conducted in the last 2 years however has indicated that these existing income inequalities have ampli ed [26]. Further research is needed to specify the association between low household income and CYP psychosocial wellbeing, especially since recent ndings indicate that mediating processes in uence this association [27].…”
Section: Participantsmentioning
confidence: 99%
“…Research conducted in the last 2 years however has indicated that these existing income inequalities have ampli ed [26]. Further research is needed to specify the association between low household income and CYP psychosocial wellbeing, especially since recent ndings indicate that mediating processes in uence this association [27].…”
Section: Participantsmentioning
confidence: 99%
“…Research exploring geographic variation in adolescent wellbeing and mental health has grown in recent years. Although there is a large number of studies investigating within-country variation (i.e., Islam et al, 2021 ; Schoon & Henseke, 2022 ; Van Phan and O’Brien, 2019 ), most research in this area focuses on cross-national differences. Evidence from cross-national studies indicate substantial variation across socio-cultural contexts and languages (Campbell et al, 2021 ; Marquez & Main, 2020 ; Rees et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies were located that examined the relationship between self-efficacy and parental educational attainment during adolescence and young adulthood in the context of the COVID-19 pandemic; none were located looking at adolescents only ( 17 , 18 ). First, general self-efficacy was not significantly associated with parental education in a sample of 16–25-year-olds in the U.K. in a survey collected from February to October 2021 ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies were located that examined the relationship between self-efficacy and parental educational attainment during adolescence and young adulthood in the context of the COVID-19 pandemic; none were located looking at adolescents only ( 17 , 18 ). First, general self-efficacy was not significantly associated with parental education in a sample of 16–25-year-olds in the U.K. in a survey collected from February to October 2021 ( 18 ). Second, researchers surveyed university students in December 2020, after the students returned to campus, and the authors found that parental education predicted students' perceived self-efficacy to prevent COVID-19 infection ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation